Virtual Communication War in Protests Against the 2024 Election Law in Indonesia: A Netnographic Study on X Hashtags - Dwi Anggoro, Ayub; Ayu Puspitasari, Fingky (Jogjakarta Communication Conference (JCC), 2025)
This study analyzes virtual communication related to opinion wars on social media concerning the rejection of the revision of the Local Government Election (Pilkada) Law in 2024 in Indonesia. A qualitative approach using a netnography method is employed to examine the contestation of two hashtags on X social media: #KawalPutusanMK and #Indonesiabaikbaiksaja. The hashtag #KawalPutusanMK is used by the public as a form of protest against the revision of the 2024 Local Government Election (Pilkada) Law, which is perceived as lacking transparency and threatening democracy. In contrast, the hashtag #Indonesiabaikbaiksaja emerged as a counter-hashtag supporting political stability and government policies. The results show that interactions on the #KawalPutusanMK hashtag are significantly higher than those on #Indonesiabaikbaiksaja, which tends to be viewed as a propaganda tool by social media users. Furthermore, the #KawalPutusanMK hashtag successfully mobilized public opinion through a strong narrative that was considered authentic, while the #Indonesiabaikbaiksaja hashtag faced many negative accusations. This research reveals how social media serves as an important arena for shaping public opinion and how perceptions of authenticity influence the effectiveness of a movement.